Reconstructing local redox conditions, mineral precipitation processes and nutrient availability in seawater during deposition of the Transvaal Supergroup, South Africa - Nke, Ansahmbom (Department of Geological Sciences, 2025)
Iron formations (IF) and carbonate rocks serve as geochemical archives, which can be used to reconstruct marine environments in the Archean and Proterozoic Eons. The chemistry of ancient oceans influenced iron redox states and primary mineral precipitation, affecting the cycling of other trace elements and nutrients. While carbonate minerals are commonly used as geochemical archives, reconstructions using IF have proved more challenging, with many studies analysing bulk powders. However, reconstructing ancient conditions is challenging due to post-depositional alteration, fine-grained mineral composition, and complex mineralogy. Recent studies highlight greenalite, an Fe(II)-silicate mineral, as a primary phase in IF and a potential proxy for ancient seawater chemistry. This study combines geochemical reconstructions from carbonate rocks with mineral-specific data from greenalite. The Transvaal Supergroup in South Africa spans the Great Oxidation Event (GOE), and provides an ideal setting for studying ancient marine chemistry due to its exceptional preservation across a range of facies. This study aims to uncover early ocean conditions by investigating carbonate and IF sequences from across a shelf environment using laser ablation inductively coupled plasma-mass spectrometry. Specifically, it explores Archean oxygen oases by studying redox-sensitive rare earth element (REE) data from contorted microbial laminae and adjacent carbonate cement from microbial carbonates, alongside a new compilation of existing data to explore the implications for pre-GOE molecular oxygen availability. A novel methodology that involves cutting along bedding planes to maximize exposure of fine-grained primary seawater phases like greenalite, combined with MATLAB code to isolate greenalite data from the enclosing chert, is used to extract accurate trace metal and REE content from primary precipitates. The trace metal content from Paleoproterozoic greenalite is then used to predict Paleoproterozoic ocean metal content. The findings from this study show that the microbial carbonates from the Campbellrand Subgroup exhibit seawater-like post-Archean Australian Shale patterns, characterized by heavy REE enrichment, small positive Eu and La anomalies, super-chondritic Y/Ho ratios, but lack Ce anomalies, indicating deposition in anoxic marine conditions. These results provide no evidence for an oxygen oasis in the Transvaal basin. However, Fe-speciation data from these carbonates show evidence for pre-GOE free molecular oxygen. This suggests that one of the proxy records is not recording primary conditions, or that cyanobacteria were producing oxygen, but it was either being consumed by aerobic processes or the environmental conditions might be too fine-scaled to be recorded by the laser ablation technique. Greenalite from the Paleoproterozoic Kuruman Formation shows heavy REE enrichment, small positive Eu anomalies, super-chondritic Y/Ho ratios, and low total REE, consistent with formation in a shelf environment. While greenalite precipitation in vent settings is possible, significant formation likely occurred on the shelf, potentially triggered by the presence of minor Fe3+, local pH increases, or warmer temperatures. High resolution data from the greenalite in this study provide quantitative constraints on marine metal concentrations in an ~2.46 Ga shelf environment, revealing drastically different patterns compared to today. Specifically, Zn and V were scarce, Ni levels were similar, Co was enriched, and Mn was highly abundant. These patterns align with thermodynamic models and other geological archives, suggesting significant impacts on early microbial evolution. This supports phylogenomic and proteomic data indicating early microbes' preference for Mn and Co over Zn. This research highlights greenalite's value as a paleo-archive and lays the groundwork for exploring the Archean and Late Proterozoic Eons to reconstruct metal concentrations across various settings and geological epochs.